2022
DOI: 10.1002/lary.30391
|View full text |Cite
|
Sign up to set email alerts
|

Phantosmia May Predict Long‐Term Measurable Olfactory Dysfunction After COVID‐19

Abstract: Objectives Persistent olfactory dysfunction (OD) after 6 months caused by SARS‐CoV‐2 infection has been reported with a variable prevalence worldwide. This study aimed to determine the prevalence of long‐term OD and identify predisposing factors. Methods A prospective cohort study was conducted on 100 adults with COVID‐19. Olfactory function was assessed with the University of Pennsylvania Smell Identification Test and a symptom survey at the onset of disease and 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“… 43 , 44 , 45 , 46 A higher prevalence of parosmia in our group of patients could be explained either by a longer OD in our population (1.4 years) or by the fact that only patients with a self‐reported long‐term OD were referred to our long‐COVID smell clinic and included in the study. Although past studies have reported a possible influence of parosmia 14 , 15 and phantosmia 10 on smell recovery our analysis did not confirm that. Similarly, in contrast with previous authors 11 , 12 , 13 , 14 , 39 we did not find any effect of age on smell recovery.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“… 43 , 44 , 45 , 46 A higher prevalence of parosmia in our group of patients could be explained either by a longer OD in our population (1.4 years) or by the fact that only patients with a self‐reported long‐term OD were referred to our long‐COVID smell clinic and included in the study. Although past studies have reported a possible influence of parosmia 14 , 15 and phantosmia 10 on smell recovery our analysis did not confirm that. Similarly, in contrast with previous authors 11 , 12 , 13 , 14 , 39 we did not find any effect of age on smell recovery.…”
Section: Discussioncontrasting
confidence: 96%
“…A meta‐analysis published in June 2022 and including articles up to October 2021 showed that female patients, subjects with greater initial severity of dysfunction or nasal congestion were less likely to recover their olfaction. 5 More recently, Leung et al 10 by using an identification test found that presence of phantosmia was associated with a worse evolution in smell recovery. In a survey conducted on 2218 COVID‐19 patients, Chudzik et al 11 found that the risk of developing persistent OD after COVID‐19 was greater in younger people with less comorbidities and a higher number of symptoms during the acute phase of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of various aspects was also included in other studies (Schwab and Fjaeldstad, 2022 ; Fjaeldstad et al, 2023 ). For instance, in the longitudinal study by Leung et al ( 2022 ) researchers addressed the frequency, impact, and intensity of symptoms, and how these symptoms changed with time.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to determine the exact percentage of long SARS-CoV-2 patients who experience olfactory disorders as anosmia, hyposmia, parosmia and phantosmia, as studies and data on the subject are still ongoing. However, a significant proportion of long SARS-CoV-2 patients have reported International Journal of Food Science and Technology 2023 olfactory and gustatory disturbances (Ohla et al, 2021;Leung et al, 2022). Cases of olfactory dysfunction have been reported from asymptomatic to severe, ranging from upper respiratory infections, to decreased acuity during aging, and anosmia (Whitcroft et al, 2020).…”
Section: Olfactory Dysfunction and Possible Effects On Quality Of Lifementioning
confidence: 99%